The Anti-Aging Properties of Panax Ginseng: A Narrative Review of Mechanisms And Clinical Evidence - Komang Ayu Silfia Budiasih; I Gede Eka Handrean (CV. Inara, 2025)
Aging is a complex physiological process influenced by various factors including oxidative stress, inflammation, and cellular damage. Natural compounds, particularly Panax ginseng, have garnered significant interest in traditional medicine for their anti-aging potential. This study aims to comprehensively review the anti-aging properties of P. ginseng, examining its traditional applications, molecular mechanisms, and clinical evidence. A narrative review methodology was employed, analyzing data from PubMed, Scopus, and Google Scholar databases, incorporating both traditional knowledge and contemporary scientific research. Results demonstrate that P. ginseng exhibits significant anti-aging effects through multiple pathways: antioxidant activity, cellular regeneration enhancement, and collagen synthesis stimulation. Ginsenosides, the primary bioactive compounds, show particular efficacy in reducing oxidative stress and supporting cognitive function. However, challenges persist in standardizing clinical applications due to variations in ginsenoside content and study methodologies. While current evidence supports P. ginseng's therapeutic potential, standardized clinical trials are essential to establish optimal dosing protocols and evaluate long-term safety. Future research should address drug interactions and efficacy across diverse populations.